Designing a Performance Measurement System Using the Balanced Scorecard Framework - Njau, Agnes (2014)
This management project research is motivated by a request from the managing director of the case study company to review and identify key corporate performance measures that should be reported periodically to the board of directors. Using process design and analysis methodology to evaluate current company practices, this dissertation will; highlight on the existing performance measures, identify new performance measures and targets for each measure and finally design a balanced scorecard framework as the performance measurement tool to be implemented in the case study company.